2018
DOI: 10.1007/s10103-018-2533-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different photobiomodulation dosimetries on temporomandibular dysfunction: a randomized, double-blind, placebo-controlled clinical trial

Abstract: Changes involving temporomandibular joint, masticatory musculature, and associated structures characterize temporomandibular dysfunction (TMD). The analgesic and anti-inflammatory effect produced by photobiomodulation has contributed to pain relief and functional improvement. However, the parameters to be used have not yet been well established. The aim of this study is to compare the efficacy of three different photobiomodulation dosimetries in the treatment of patients with TMD. A randomized, double-blind, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(101 citation statements)
references
References 29 publications
1
84
0
16
Order By: Relevance
“…All studies evaluated the outcomes at baseline and after the treatment protocol 61 , with number of sessions varying from 1 week to 1 year. Pain levels were assessed as the primary outcome in all studies using Visual Analogic Scale (VAS) in 29 (83%) studies 1,2,10,15,16,22,24,25,31,33,36,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][61][62][63][64] or an algometer to evaluate the pressure pain threshold in 5 (14%) studies 2,36,46,58,62 ; one study (3%) used the Verbal Pain Scale 59 . The results of an intragroup analysis demonstrated that 27 (77%) 5,10,20,22,24,25,27,31,33,36,44...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies evaluated the outcomes at baseline and after the treatment protocol 61 , with number of sessions varying from 1 week to 1 year. Pain levels were assessed as the primary outcome in all studies using Visual Analogic Scale (VAS) in 29 (83%) studies 1,2,10,15,16,22,24,25,31,33,36,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][61][62][63][64] or an algometer to evaluate the pressure pain threshold in 5 (14%) studies 2,36,46,58,62 ; one study (3%) used the Verbal Pain Scale 59 . The results of an intragroup analysis demonstrated that 27 (77%) 5,10,20,22,24,25,27,31,33,36,44...…”
Section: Discussionmentioning
confidence: 99%
“…The results of an intragroup analysis demonstrated that 27 (77%) 5,10,20,22,24,25,27,31,33,36,44,45,46,47,50,[52][53][54][55][56][57][58][59][60][61][62][63] of the studies presented reduction in pain and 22 (62%) 2,5,10,15,20,24,25,31,36,[44][45][46][47][52][53][54]56,57,59,60,62,64 , improvement in function. Among them, LLLT (34%) 2,515,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then 55 potentially eligible articles were obtained by screening the titles and abstracts carefully. After careful full-text screening and assessment of the risk of bias, 20 RCTs met the inclusion criteria [4,10,12,15,28,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. This selection process and exclusion reasons were presented in the ow chart (Fig.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Uma possível explicação para a redução dos espasmos na musculatura da ATM tratada com fotobiomodulação pode estar associada aos níveis de energia absorvida nos citocromos e porfirinas dentro da mitocôndria e membrana celular dessas células. Tais níveis de energia disponibilizarão uma pequena quantidade de oxigênio extra dentro da célula, acelerando a glicólise e a oxidação fosforilativa com maior disponibilização de ATP, além da ativação da microcirculação, que, pela ação da histamina liberada por meio da ação do próprio laser, proporcionará mais nutrientes para que essas células possam aperfeiçoar seu metabolismo 5,9. Assim, o objetivo deste artigo é relatar um caso clínico utilizando a fotobiomodulação no tratamento da disfunção temporomandibular proporcionando analgesia e maior abertura bucal.RELATO DE CASOPaciente do gênero fem i ni no, 24 a nos, estudante universitária, se apresentou ao projeto de extensão "Laserterapia na Odontologia", realizado na Universidade Federal do Maranhão/ Brasil, com cefaleia e fortes dores bilaterais na face.…”
unclassified